Case Study: Public Satisfaction with Land Acquisition at Komodo Airport, Labuan Bajo, West Manggarai, Indonesia - Abel Asa Mau; Thomas Bustomi; Nursalam (Eximia, 2024)
The quality of public services is a variable that affects general satisfaction. Land acquisition for the development of Labuan Bajo Airport seeks to maintain a dynamic relationship between developers and land owners. This research focuses on 5 (five) indicators of public satisfaction with the airport development process, including aspects of tangibles, Reliability, responsiveness, assurance, and empathy. This study used a qualitative observational approach. The data collection method used interviews, surveys, observations, and Focus Group Discussions on airport service users. The study results show that five indicators, tangibles, Reliability, responsiveness, assurance, and empathy, have been carried out well in implementing land acquisition for airport development.